Isolation and Purification of Dehalogenase From Pseudomonas cepacia UK7WS1 strain - Tatang Hernawan; S. Soemitro S. Soemitro; H. Dewayani H. Dewayani; Tetih Tetih; W. T. Ismaya (Institut Teknologi Bandung, 1999)
Intracellular dehalogenase enzyme had been isolated from Pseudomonas cepacia UK7WS1 strain which was grown in MSM broth containing yeast extract (0.18 g/L) and MCPA (0,02 g/L) and incubated for 22-24 h at 30 oC. Enzyme purification was carried out by ammonium sulphate fractionation, DEAE-cellulose column chromatography and Sephadex G-75 gel filtration column chromatography. Protein purify factor achieved was 12.4 times and protein yield was 10 % w/w of the crude cell extract protein. The enzyme purity of each purification stage was monitored by SDS-polyacrylamide gel electrophoresis and resulted in one protein band for each denatured enzyme (dimeric protein of two identical subunits) and non-denatured enzyme (monomeric protein subunit).